Characterization of Three L-Asparaginases from Maritime Pine (Pinus pinaster Ait.) - Van Kerckhoven, Sonia H.; de la Torre, Fernando N.; Cañas, Rafael A.; Avila, Concepción; Cantón, Francisco R.; Cánovas, Francisco M. (Frontiers in Plant Science, 2017)
Asparaginases (ASPG, EC 3.5.1.1) catalyze the hydrolysis of the amide group of L-asparagine producing L-aspartate and ammonium. Three asparaginases, PpASPG1, PpASPG2 and PpASPG3, have been identified in the transcriptome of maritime pine (Pinus pinaster Ait.) that were transiently expressed in Nicotiana benthamiana by agroinfection. The three recombinant proteins were processed in planta to active enzymes and it was found that all mature forms exhibited double activity asparaginase/isoaspartyl dipeptidase but only PpASPG1 was able to catalyze efficiently L-asparagine hydrolysis. PpASPG1 contains a variable region of 77 amino acids that is critical for proteolytic processing of the precursor and is retained in the mature enzyme. Furthermore, the functional analysis of deletion mutants demonstrated that this protein fragment is required for specific recognition of the substrate and favors enzyme stability. Potassium has a limited effect on the activation of maritime pine asparaginases what is consistent with the lack of a critical residue essential for interaction of cation. Taken together, the results presented here highlight the specific features of asparaginases from conifers when compared to the enzymes from angiosperms.